2022
DOI: 10.3389/fpls.2022.878908
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Physico-Chemical and Microbiological Properties During Natural Succession: A Case Study in Lower Subtropical China

Abstract: Vegetation succession can change the function and quality of the soil. Exploring the changes in soil properties during secondary forest restoration is of great significance to promote forest restoration and improve the ecological service function of subtropical ecosystems in South China. In this study, we chose three typical forests in subtropical China as restoration sequences, broadleaf–conifer mixed forest (EF), broad-leaved forest (MF), and old-growth forest (LF), to study the changes in soil physico-chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Our results showed that in the vertical soil profile of different study sites, AK, AN, and AP had a downward trend (Fig. 5), this is probably because of soil leaching characteristics and changes in the soil microbial and biomass (Zhao et al, 2022a). In addition, deeper soil obtains limited nutrients from the decomposition of litter, resulting in higher nutrients in topsoil layer (Zhao et al, 2022b).…”
Section: Soil Properties In Different Ecological Restoration Patternsmentioning
confidence: 76%
“…Our results showed that in the vertical soil profile of different study sites, AK, AN, and AP had a downward trend (Fig. 5), this is probably because of soil leaching characteristics and changes in the soil microbial and biomass (Zhao et al, 2022a). In addition, deeper soil obtains limited nutrients from the decomposition of litter, resulting in higher nutrients in topsoil layer (Zhao et al, 2022b).…”
Section: Soil Properties In Different Ecological Restoration Patternsmentioning
confidence: 76%
“…In general, SOM, which is made up of approximately 58% soil organic carbon, is associated with an increased water-holding capacity (strong positive correlation) in the surface horizon of agricultural soil [55]. The correlation between SOC and SWC is evident within soil aggregates, as demonstrated by Panagea et al and Zhao et al [56,57]. These aggregates are formed through the accumulation of SOM molecules and mineral particles, as elucidated in the study by Abiven et al [58].…”
Section: Effect On Soil Water Contentmentioning
confidence: 83%
“…Enhanced porosity is believed to improve soil aeration, creating a more optimal environment for soil microorganisms by facilitating gas exchange and potentially mitigating limitations caused by low oxygen availability (Zhao et al, 2022). Soil compaction, often caused by heavy machinery or unsustainable cropping practices, negatively impacts soil physical properties, potentially hindering microbial activity and essential biochemical processes crucial for nutrient availability.…”
Section: Discussionmentioning
confidence: 99%